MEMBANDINGKAN TEGANGAN PERMUKAAN DENGAN TEGANGAN AIR MENGGUNAKAN ZAT PEWARNA MAKANANAN SEBAGAI ALAT PERAGA PEMBELAJARAN - Asmawati, Eka Yulisari (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
Have performed experiments to compare the surface tension of water by the surface tension of alcohol use food dye. The research method is to perform a simple test. With a drop of food dye into water will make the water molecules become larger and when alcohol was dropped into the solution there will be a tug between water and alcohol with water or with alcohol-called cohesion. Tug between different molecules such as water to alcohol is called adhesion. Cohesion of water molecules is greater than the cohesion of the alcohol molecules. Cohesion of water is also greater than the adhesion between the two fluids. Competition between cohesion and adhesion molecules of water and alcohol lead to mutual attraction between water and alcohol resulting in vibrations when the fluid is met. The results obtained when this trial is water that has spilled food dye will move away from the alcohol and water colored parts that come into contact with alcohol will vibrate.